Risk for nitrogen leaching after application of solid manure in autumn differs between manure types - Delin, Sofia; Mårtensson, Kristina; Johnsson, Holger (Frontiers in Environmental Science, 2024)
Manure application performed in autumn requires regulation due to the risk of nitrogen (N) leaching during winter. On the other hand, application of manure in spring can pose some practical problems depending on the risk for N immobilization and the difficulty in ploughing heavy clay soils during this time of year. The risk for leaching is likely to differ between different soil texture and manure characteristics. In this study, we sought to estimate the risk for nitrogen leaching depending on the carbon/nitrogen ratio (C/N) of the manure, time for manure application, and soil type. We combined 3-year lysimeter experiments with 2-year field plot experiments and laboratory soil incubations and compared results with those from an empirical model. We compared effects of manure application on two soils (silty clay and loamy sand) and solid manures with different representing C/N ratios. In incubations, only manure with a C/N-ratio below 14 contributed with significant amounts of leachable N during the first months after application. In the lysimeter study, N leaching was unaffected by the timing of the application of the manure with C/N-ratio 18. However, regarding manure with C/N-ratio 10, N leaching was elevated with 10–15 kg N per ha after manure application in October compared to November and March on both soil types. The mineral N analyses from soil profiles in the field experiments showed a similar pattern, however, the increase was higher on the loamy sand compared to the silty clay. The ammonia emissions did not differ between manure types, but were on average 24% of applied NH4-N after application in October when air temperature was on average 12°C compared to only 3% of applied NH4-N in November and March when air temperature was on average 5°C. Similar to lysimeter results, the modelled N leaching was higher the earlier the manure application occurred in autumn. However, the model also predicted increased leaching for the manure with a high C/N-ratio, and a smaller effect on leaching on clay soil. Considering this, the model calculations overestimated the leaching effects from manure with a high C/N-ratio and underestimated the leaching effects on clay soil.